The Laws of Trading - Lebron, Agustin (Ascent Audio, 2019)
Trading books generally break down into two categories: the ones which claim to teach you how to make money trading, and the memoir-style books recounting scandals and bad behavior. But the former don't have profitable trades to teach; if they did they'd keep those trades to themselves. And the latter are frequently entertaining, but they don't leave you with much you can apply in your own life. The Laws of Trading is different. All of our relationships and decisions involve trading at some level. This is a book about decision-making through the lens of a professional prop trader. For years, behavioral and cognitive scientists have shown us how human decision-making is flawed and biased. But how do you learn to avoid these problems in day-to-day decisions where you have to react in real-time? What are the important things to think about and to act on? The world needs a book by a prop trader who has lived, breathed, and taught trading for a living, drawing upon years of insights on the trading floor in real markets, good and bad, whether going sideways, crashing, or bubbling over. If you can master the decision-making skills needed to profitably trade in modern markets, you can master decision-making in all walks of life. This book will teach you exactly those skills.
Online resource; Title from title page (viewed July 30, 2019)
Keywords: Investment analysis; Business; Investments -- Decision making; Analyse financière; Affaires; Investissements; Prise de décision; Investments; Decision making; Audiobooks